Sistem Kontrol Elektronik pada Rumah Pintar Dengan Input Suara pada Module Pengenalan Suara V3 Berbasis IoT - Feriman; Banu Santoso (AI Society & STMIK Indonesia, 2024)
This research aims to develop and implement an electronic control system for a smart home based on IoT, utilizing the Voice Recognition Module v3. The system is designed to allow users to operate electronic devices at home through voice commands recognized by the module, which are then transmitted to the Arduino to turn connected devices on or off. Additionally, the system is integrated with the Telegram application, enabling remote control of devices. Testing results indicate that the system is highly effective in recognizing voice commands, with a high success rate, and functions optimally through both voice input and the Telegram application. Therefore, this system offers an efficient solution for managing smart homes, particularly in enhancing the convenience and efficiency of daily electronic device usage.